(untitled) (Quest Journal of Management and Social Sciences, 2022)
Purpose- This paper aims to identify the current status of training factors in Banking sectors and to examine the mediating effect of learning performance on the relationship between training factors and transfer performance. Design/methodology/approach- This study followed the positivist epistemology. Following a descriptive and casual research design, we collected the data at two different points in time with the same respondents. Responses were collected on a stratified basis. Findings- The findings indicate the significant mediating role of learning performance in training factors (i.e. self-efficacy, trainee motivation, training content, trainer’s characteristics, supervisors support and continuous learning culture) and transfer performance relationship. Practical implication- The banking sector could be in the best position by identifying the dominant factor for transfer performance. Furthermore, this study helps decision-makers decide efficiently by identifying the root causes of performance transfer. Trainers having adequate knowledge and supervisor support could make the training content interesting, practical and valuable for better job performance. Banking sectors could identify the important motivation factors like intrinsic/extrinsic rewards, career-focused training, and necessary materials needed for training which are the root causes of transfer performance.